On the Use of Attributes to Manage Requirements. Issue 5 (22nd November 2016) - Wheatcraft, Louis S.; Ryan, Michael J.; Dick, Jeremy
ABSTRACT: There are many sources in systems engineering and requirements engineering that use the term "attribute, " but few define the term and fewer actually go into any detail regarding how the attributes might be applied to requirement statements. This paper addresses the inconsistent definition and use of the term as part of the systems engineering and requirements engineering processes. We discuss the importance of defining requirement attributes and offer a useful definition. We provide a possible list of attributes along with their meaning, in order to provide a useful set of attributes that organizations may include with requirement expressions to manage better their requirements. Finally, we discuss how attributes can be used to manage not only requirements and sets of requirements, but also the project.